Learning IFAM by using ITS Medical Centre as a Case: #1 - Identifying the Function, Medical Service, Infrastructure & Facility - Vita Ratnasari; Hitapriya Suprayitno (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
Nowadays, Infrastructure & Facility Asset Management (I&FAM) is essential in Indonesia. Indonesian Law on State Treasury was decreed in 2014, which makes the term I&FAM still relatively new in Indonesia. Therefore, the researcher must develop about I&FAM studies, such as doing a practice. For example, the ITS Medical Center (MCITS) use as a case for learning I&FAM. The first step is to identify the statement of the function, the service, and the infrastructure & facility. This research used a straightforward method by reading related document and reconnaissance survey. The research produces three principal results, giving medical service for the ITS' community and the surrounding area, and giving another income for ITS. The ITS Clinic occupies a special clinic building of 2 stories high, equipped with a garage, parking lot and a sign. As a facility, the clinic is equipped with a building, the building facilities, standard clinic medical equipment, and an ambulance.